Two-component γ-Ray Emission Spectrum and X-Ray Polarization of the Radio Galaxy Pictor A - Jia-Xuan Li; Xin-Ke Hu; Ji-Shun Lian; Yu-Wei Yu; Wei Deng; Kuan Liu; Hai-Ming Zhang; Liang Chen; Jin Zhang (The Astrophysical Journal, 2025)
Pictor A is a γ -ray emitting radio galaxy and has a bright hotspot called the western hotspot (WHS), located ∼4′ away from the nucleus. In this work, we present an analysis of its 16 yr Fermi Large Area Telescope (LAT) data and report the Imaging X-ray Polarimetry Explorer (IXPE) observations for this source. Our analysis of the Fermi-LAT observations reveals evidence of two components in the average γ -ray spectrum of Pictor A, exhibiting a statistically significant hardening from Γ _γ _,1  = 3.25 ± 0.15 to Γ _γ _,2  = 1.81 ± 0.07 at a break energy of 2.46 ± 0.09 GeV. Notably, variability of γ -rays is evident in Pictor A, predominantly driven by the component below the break energy, while the component above the break energy remains stable. Furthermore, our analysis reveals that a power-law function provides an adequate fit for the high-flux-state spectrum, while a broken-power-law function remains necessary to accurately model the low-flux-state spectrum. We suggest that the low-energy component originates from the nucleus, while the high-energy component primarily stems from WHS. The broadband spectral energy distributions of both nucleus and WHS can be well represented by a simple leptonic model, with both γ -ray components attributed to the synchrotron self-Compton (SSC) process. Analysis of IXPE data provides upper limits on the polarization degree of Π _X  < 6.6% for the nucleus and Π _X  < 56.4% for the WHS within the 2–8 keV band. For the nucleus, this result aligns with X-ray emission originating from the SSC process. However, the upper limit of Π _X  < 56.4% for WHS is insufficient to conclusively determine the X-ray emission mechanism in this region.